Quark-Antiquark Study with Inversely Quadratic Yukawa Potential Using the Nikiforov-Uvarov-Functional-Analysis Method - Inyang, Etido P.; Iwuji, Prince C.; Ntibi, Joseph E.; Omugbe, E.; Ibanga, Efiong A.; William, Eddy S. (East European Journal of Physics, 2022)
The solutions of the Schrödinger equation are obtained with an inversely quadratic Yukawa potential using the Nikiforov-Uvarov-Functional-analysis method. The energy spectrum and wave function were obtained in closed form. The energy equation was used to predict the masses of the heavy mesons such as charmonium (сĉ) and bottomonium (bḃ) for different quantum numbers. The results obtained agreed with other theoretical predictions and experimental data with a percentage error of 1.68 % and 0.50 % for charmonium (сĉ) and bottomonium (bḃ) respectively.